How the System of Environmental-Economic Accounting can improve environmental information systems and data quality for decision making. Issue 89 (November 2018) - Vardon, Michael; Castaneda, Juan-Pablo; Nagy, Michael; Schenau, Sjoerd
Highlights: Integration of environmental and economic data is essential for improved decision making. The System of Environmental-Economic Accounting increases the use of environmental information. The System of Environmental-Economic Accounting increases data quality. Abstract: The System of Environmental-Economic Accounting (SEEA) is a framework integrating information from different sources with the aim of enabling better decision making by governments, business and others. Accounting allows a wide variety of data to be synthesised so that regular information and indicators are produced and can feed into decision-making processes. The accounting recognises that while there may be discrepancies between different data sources as well as data gaps, government and business must continually make decisions. Over time both the accounts and underlying data improves across the six dimensions of data quality – relevance, accuracy, timeliness, accessibility, interpretability and coherence. In individual data sources the focus is mostly on accuracy (i.e. closeness of estimate to the real number) but accounting addresses all of the six dimensions and has particular strengths in timeliness, accessibility, interpretability and coherence providing data when it is needed in a consistent format. Using examples from high and low-income countries we describe how SEEA can improve information systems and data quality for decision making and distil lessons for the development of the European Shared Environmental Information System.